SARS CoV-2 Organotropism Associated Pathogenic Relationship of Gut-Brain Axis and Illness - Shinu, Pottathil; Morsy, Mohamed A.; Deb, Pran Kishore; Nair, Anroop B.; Goyal, Manoj; Shah, Jigar; Kotta, Sabna (Frontiers in Molecular Biosciences, 2020)
COVID-19 has resulted in a pandemic after its first appearance in a pneumonia patient in China in early December 2019. As per WHO, this global outbreak of novel COVID-19 has resulted in 28,329,790 laboratory-confirmed cases and 911,877 deaths which have been reported from 210 countries as on 12th Sep 2020. The major symptoms at the onset of COVID-19 are fever (98%), tussis (76%), sore throat (17%), rhinorrhea (2%), chest pain (2%) and myalgia or fatigue (44%). Furthermore, acute respiratory distress syndrome (61.1%), cardiac dysrhythmia (44.4%), shock (30.6%), hemoptysis (5%), stroke (5%), acute cardiac injury (12%), acute kidney injury (36.6%), dermatological symptoms with maculopapular exanthema (36.1%) and death can occur in severe cases. Even though human coronavirus (CoV) is mainly responsible for infections of the respiratory tract, some studies have shown CoV (in case of SARS and MERS) to possess potential to spread to extra-pulmonary organs including the nervous system as well as GIT. Patients infected with COVID-19 have also shown symptoms associated with neurological and enteric infection like disorders related to smell/taste, loss of appetite, nausea, emesis, diarrhea and pain in the abdomen. In the current review, we attempt to summarize the understanding of basic mechanisms involved in clinical manifestations of COVID-19, mainly focusing on interaction of COVID-19 with gut-brain axis. By combining our knowledge of the biological features of the virus with clinical findings, we can improve our understanding of the potential mechanisms underlying COVID-19, paving the way towards the development of preventative and therapeutic solutions.